Progress in search for high-redshift galaxies magnified by gravitational lensing - Zheng, Wei; Zitrin, Adi (Astronomische Nachrichten, 2013)
Our searches in the CLASH data have found many high-redshift galaxy candidates. One object at z = 6.2 in MACS J0329-02 is quadruply lensed. Another object in MACS J1149+22 is at redshift z = 9.6 and AB = 25.7, the first candidate at z > 9 that is bright enough for spectroscopic observations. The discovery of more than 80 galaxy candidates at z > 7 demonstrates the unique potential of galaxy cluster fields for finding highly magnified, intrinsically faint galaxies at the highest redshifts.